Seren taun Sebagai Medium Komunikasi Adat - Abdul Malik (LONTAR: Jurnal Ilmu Komunikasi, 2017)
Seren taun is a traditional ceremony performed by Kasepuhan Cisungsang, Banten Kidul, as a vehicle to give thanks to God Almighty for their harvest. In the perspective of intracultural communication. Seren taun is an indigenous communication medium that serves to transform the values of adat from one generation to the next for the preservation of their cultural identity. Therefore, every ceremony of ceremonial seren taun must be attended and followed by all members of indigenous communities without exception, either living in custom territory or outside customary territory. Meanwhile, in the perspective of intercultural communication, seren epidemic ceremony becomes a medium for the existence of adat, so that its existence is accepted, acknowledged, and protected by the state.This study focuses on understanding: First, how the kasepuhan community makes seren taun as a medium of communal communication in order to reinforce their cultural identity. Second, how the society kasepuhan make seren epidemic as a medium of communication for the sake of existence. Based on these two questions, it is understood that seren taun has expanded its function. As a form of respect for the earth (land) and thankfulness of the harvest, as well as the symbolic form of existence of society. The existence of expansion of function in seren taun, based on awareness affirming identity as indigenous peoples with all its distinctive style and culture, which is not owned by other society entity, as well as contestation of their cultural identity to other party for the sake of existence of adat. Keywords: Seren Taun, Kasepuhan Cisungsang, Cultural Identity, Customary Existence